1239. Different Dose Levels of a Respiratory Syncytial Virus Maternal Vaccine Candidate (RSVPreF3) Administered to Non-pregnant Women in a Randomized Clinical Trial Are Immunogenic and Well Tolerated. (31st December 2020) - Schwarz, Tino; Johnson, Casey; Grigat, Christine; Apter, Dan; Csonka, Peter; Lindblad, Niklas; Nguyen, Thi Lien-Anh; Gao, Feng F; Soni, Jyoti; Tullio, Antonella Nadia; Dieussaert, Ilse; Picciolato, Marta; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a leading cause of bronchiolitis and pneumonia in childhood. Maternal immunization could help to protect infants from RSV-associated infections in their first months of life. We evaluated the safety, reactogenicity and immunogenicity of the RSV maternal (RSVPreF3) vaccine candidate in non-pregnant women, at different dose levels. Methods: In this phase I/II, observer-blind, multicenter study (NCT03674177), healthy non-pregnant women aged 18–45 years were randomized (1:1:1:1) and received 1 dose of either 30, 60 or 120 µg of RSVPreF3 vaccine (30/60/120 RSVPreF3 group) or placebo. Solicited adverse events (AEs) (until day 7 [D7] post-vaccination), unsolicited AEs (until D30 post-vaccination), hematological and biochemical laboratory abnormalities (at D8 and D31 post-vaccination) were recorded. Serious AEs (SAEs) were collected until D181 and immune responses until D91 post-vaccination. Exploratory analysis was performed at D31 to compare immunogenicity of different dose levels. Results: 502 women were included in the exposed set. The most frequently reported solicited AEs were pain and headache (Fig 1 ). Grade 3 solicited AEs were infrequently reported. 180 women experienced unsolicited AEs; 19 reported grade 3 unsolicited AEs, among which 1 was vaccination-related (60 RSVPreF3). 3 SAEs were reported (1 in 120 RSVPreF3; 2 in placebo); none was related to vaccination. No clinically significant changes in laboratory parameters occurred. Geometric mean titers of anti-RSV A neutralizing antibody (≥ 8-fold at D8 and ≥ 5-fold until D91 vs baseline) and geometric mean concentrations of anti-RSVPreF3 IgG antibody (≥ 12-fold at D8 and ≥ 6-fold until D91 vs baseline) were boosted in all RSVPreF3 groups (Fig 2, 3 ). The 60 and 120 µg dose levels of RSVPreF3 were significantly more immunogenic than the 30 µg one. Figure 1. Solicited adverse events until day 7 post-vaccination Figure 2. GMTs of anti-RSV A neutralizing antibody (ED60) until day 91 post-vaccination Figure 3. GMCs of RSVPreF3 IgG antibody (EU/mL) until day 91 post-vaccination Conclusion: All RSVPreF3 vaccine dose levels were well tolerated and no safety concerns identified. All 3 dose levels were immunogenic, with higher immune response induced by the 60 and 120 µg dose levels than the 30 µg one. These data support the further investigation of the 60 and 120 µg RSVPreF3 dose levels in pregnant women. Funding: GlaxoSmithKline Biologicals SA Acknowledgment: N Bulik/Q Deraedt (Modis c/o GSK) provided writing/editorial support Disclosures: Tino Schwarz, PhD, GSK group of companies (Scientific Research Study Investigator, Speaker's Bureau) Christine Grigat, MD, GSK group of companies (Scientific Research Study Investigator) Dan Apter, MD, PhD, GSK group of companies (Research Grant or Support) Peter Csonka, MD, PhD, GSK group of companies (Scientific Research Study Investigator) Thi Lien-Anh Nguyen, PhD, GSK group of companies (Employee, Shareholder) Feng F. Gao, PhD, GSK group of companies (Employee) Jyoti Soni, MA, GSK group of companies (Employee) Antonella Nadia Tullio, Dr., GSK group of companies (Employee) Ilse Dieussaert, IR, GSK group of companies (Employee, Shareholder) Marta Picciolato, PharmD, MSc, GSK group of companies (Employee) Ouzama Henry, MD, GSK group of companies (Employee, Shareholder)